(untitled) (REMUNOM, 2025)
Artificial intelligence is one of the information and communication technologies that has promoted major transformations in organizations and their production processes, especially material handling. The growing number of published studies led to the development of this study, which aimed to describe the main characteristics of studies that report the application of artificial intelligence in material handling. The method used was the conceptual bibliographic, bibliometric design based on four stages: formulation of research questions, collection of bibliographic data, analysis, organization of the collected data, and generation of answers to the guiding questions. The results showed that the focuses of the applications are a) improvement and optimization of the logistics process, increased rationality of human-machine actions, and optimization of the decision-making process, b) use of several simultaneous methods and techniques, c) facing problematic situations aimed at problem-solving and generation of technologies, d) application of multiple artificial intelligence tools, e) successful results have increased competitiveness and rationality in material handling and f) opening for new and interconnected applications. The conclusion shows that using artificial intelligence has provided an environment for enhancing human cognitive capacity. The main contribution of this study to science is the finding that professional training in logistics needs to incorporate mastery of artificial intelligence.